The influence of the ricorse - PBL ( Problem Based Learning ) model on cognitive learning outcomes, creative thinking and critical thinking in ecology and biodiversity materials - Sumah, Vonissa; Rumahlatu, Dominggus; Liline, Sintje (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2024)
One of the competencies of educators as the key to success in learning is improving the quality of learning through selecting and using appropriate learning models to empower students' abilities. The learning model that can be used is an integrated learning model between the Ricorse model and PBL (Problem Based Learning) which can construct students' knowledge through efforts to solve problems that exist in the real world. This research aims to determine the effect of the Ricorse - PBL learning model on cognitive learning outcomes, creative thinking and critical thinking on ecology and biodiversity material in class VII junior high school students in Ambon City. The research method used was a quasi experiment with the population in this study being all students in class VII of Junior High School 13 Ambon, Junior High School 3 Ambon and Junior High School 19 Ambon, each class consisting of 30 students so that the total sample was 180 students. The research instrument uses test instruments and LKPD. Data analysis in this study used covariance analysis (Ancova) with SPSS Version 23 software. The results of the study showed that the Ricorse learning model integrated with PBL had a joint effect on the learning outcomes, creative thinking and critical thinking of class VII students at Junior High School 13 Ambon. , Junior High School 3 Ambon and Junior High School 19 Ambon in studying ecology and biodiversity material with a significant value of 0.000<0.05.